Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3389/fnut.2019.00082
|View full text |Cite
|
Sign up to set email alerts
|

Heart Failure and a Plant-Based Diet. A Case-Report and Literature Review

Abstract: A 54-year-old female with grade 3 obesity body mass index (BMI 45.2 kg/m 2 ) and type II diabetes (hemoglobin A1c 8.1%) presented to her primary care physician in May 2017 with a chief complaint of left lower extremity edema. Work-up revealed heart failure with depressed left ventricular systolic function. Upon diagnosis, she substantially altered her lifestyle, changing her diet from a “healthy western” one to a whole food plant-based one. Guideline directed medical therapy for heart fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 120 publications
0
12
0
Order By: Relevance
“…There is interventional and observational evidence that a plant‐based diet may decrease the incidence and severity of heart failure . More recently, several case reports on plant‐based diets as a potential therapeutic approach in the treatment of heart failure have been published . While well‐designed and large randomized, controlled nutrition intervention trials are missing with regard to this entity, a series of potential mechanisms on how a plant‐based diet may beneficially affect heart failure have been postulated .…”
Section: Risk Factor Modification Through Dietary Modificationmentioning
confidence: 99%
See 1 more Smart Citation
“…There is interventional and observational evidence that a plant‐based diet may decrease the incidence and severity of heart failure . More recently, several case reports on plant‐based diets as a potential therapeutic approach in the treatment of heart failure have been published . While well‐designed and large randomized, controlled nutrition intervention trials are missing with regard to this entity, a series of potential mechanisms on how a plant‐based diet may beneficially affect heart failure have been postulated .…”
Section: Risk Factor Modification Through Dietary Modificationmentioning
confidence: 99%
“…80 More recently, several case reports on plantbased diets as a potential therapeutic approach in the treatment of heart failure have been published. 85,86 While well-designed and large randomized, controlled nutrition intervention trials are missing with regard to this entity, a series of potential mechanisms on how a plant-based diet may beneficially affect heart failure have been postulated. 80 These include decreased oxidative stress and inflammation levels, increased nitric oxide bioavailability, reduced homocysteine levels, and increased levels of antioxidants.…”
Section: Heart Failure and Coronary Artery Diseasementioning
confidence: 99%
“…5 What is of paramount importance is that even cases of disease reversal have been described. 6 A concise review by Kerley recently discussed the role of a whole-food plant-based (vegan) diet high in the treatment of heart failure. 5 While low in saturated-and transfats, such diets are rich in antioxidants, micronutrients, fiber and nitrate -which all may beneficially affect heart failure.…”
Section: Dear Editormentioning
confidence: 99%
“…4 While large and well-designed randomized, controlled nutrition intervention trials specific to heart failure are yet missing, 5 several case reports emphasized the promising potential of a whole-food plantbased (vegan) diet in the treatment of this entity. 6,7 Najjar and Montgomery very recently published three cases where such a diet was combined with standard medical treatment for heart failure. 7 In all cases, the authors observed a significant increase in ejection fraction, stroke volume and cardiac output, as assessed by magnetic resonance images.…”
Section: Dear Editormentioning
confidence: 99%
“…However, these therapies often neglect the underlying maladaptive cellular processes that underlie HF. Plant-based diets have been associated with reduced cardiovascular disease (CVD) risk independent of physical activity [6], inflammation [7,8], and may even be a viable adjunct treatment of HF, improving EF and decreasing LV mass [9][10][11]. Indeed, the consumption of a Mediterranean diet and the Dietary Approaches to Stop Hypertension (DASH) diet, which are characterized by increased fruit and vegetable intake, is associated with reduced incidence of HF and cardiac deaths [12].…”
Section: Introductionmentioning
confidence: 99%